L`impact de supplémentations en probiotiques sur les capacités aérobies et la masse musculaire des athlètes : méta-analyse - Guo, C.; Luo, S.; You, Y. (Science & Sports, 2026)
Objective This study primarily evaluated the impact of probiotic supplementation on aerobic capacity and muscle mass in athletes.